Criminal Liability Of Actors Who Participate In Terrorism Criminal Acts In Indonesia - Sri Utami; Yasmirah Mandasari Saragih; Mhd. Azhali Siregar; Darma Setiawan; Juita Novalia Br Barus (International Journal of Sociology and Law, 2024)
The crime of terrorism is a form of crime with an international dimension that is very frightening to the public. Terrorism is a crime against humanity which is classified as an extraordinary crime because it has succeeded in creating chaos based on religion, sect or organization. This crime against humanity is regulated in Law of the Republic of Indonesia Number 5 of 2018 concerning Terrorism Crimes. Terrorist networks that are difficult to trace and have wide access make the problem of terrorism difficult to eradicate. Easy access between countries is one of the reasons why it is difficult to break the chain of terrorist networks. So efforts are needed through bilateral, regional and international cooperation to eradicate terrorism. The research method used in this paper uses normative legal research based on legal theories. By taking a legislative approach through literature study. This research aims to find out what causes perpetrators to commit criminal acts of terrorism and to find out what form of criminal law accountability exists for perpetrators who participate in criminal acts of terrorism in Indonesia.